2010
DOI: 10.1016/j.jcv.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and evaluation of an influenza A (H5) pseudotyped lentiviral particle-based serological assay

Abstract: H5pp provide a reliable and safe alternative for sero-diagnosis and sero-epidemiology of H5N1 infections in a BSL-2 setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…We explored the kinetics of the serological responses to this novel virus in haemagglutination inhibition (HI) assays and in a recently developed H7N9 pseudotype virus particle neutralisation (Nab) test [10]. Viral pseudotypes have been previously shown to provide reliable correlation with conventional microneutralisation tests for influenza A(H5N1) serological studies [11]. We investigated correlations between serological responses and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We explored the kinetics of the serological responses to this novel virus in haemagglutination inhibition (HI) assays and in a recently developed H7N9 pseudotype virus particle neutralisation (Nab) test [10]. Viral pseudotypes have been previously shown to provide reliable correlation with conventional microneutralisation tests for influenza A(H5N1) serological studies [11]. We investigated correlations between serological responses and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are many studies that support the use of retroviral pseudotypes bearing hemagglutinin (HA) as a substitute for influenza viruses in neutralization assays whose application allows the work in a Biosafety Level 2 environment. In such studies, it has been demonstrated that neutralization of retroviral pseudotypes is as sensitive and specific as the HI and MN using live virus, proving to be a valid alternative for the detection and quantification of neutralizing antibodies against different influenza virus subtypes (6,27,29,30). In the same way, Temperton and colleagues demonstrated that the results of assays using retroviral pseudotypes bearing HA for determining H5N1 neutralizing antibodies in sera from humans that recovered from infection and sera from animals experimentally immunized correlated with those from HI and MN (29).…”
Section: Discussionmentioning
confidence: 99%
“…Beta prior 216 distributions were defined using informative prior information for the Se and Sp of the H5pp 217 VNT test (based on Garcia and al, 2010) and the prevalence of the 2 populations (unpublished 218 data from author Desvaux) (see Table 1 for details). Non informative priors were used for the 219 Se and Sp of HI test and the correlation between tests (beta distributions (1,1) equivalent to 220 uniform distributions (0,1)).…”
Section: Bayesian Inference 215mentioning
confidence: 99%